Fair trade consumption from the perspective of US Baby Boomers - Benson, Ebony; Hiller Connell, Kim Y. (My University, 2014)
Purpose – The purpose of this study is to expand the knowledge base of Baby Boomers’ attitudes, behaviours and perceived barriers related to fair trade purchasing. Design/methodology/approach – This study included 168 Baby Boomers. Data were collected through an online questionnaire. Data analysis included a combination of both quantitative (descriptive statistics, independent samples t-tests and correlation analysis) and qualitative techniques. Findings – Findings indicated that the participants exhibited positive attitudes towards fair trade but were minimally engaged in fair trade purchasing. Furthermore, the participants perceived numerous barriers to purchasing fair trade products including the incompatibility of fair trade merchandise with lifestyles, the inability to touch and see fair trade products prior to purchase and difficulty in identifying fair trade items. Research limitations/implications – A limitation of this study is that the sample was well-educated university faculty and it is not representative of all Baby Boomers. Practical implications – Fair trade entities need to be more effective in marketing the advantages of the fair trade. Fair trade organizations should consider targeting marketing strategies specific to the unique demographic and psychographic characteristics of Baby Boomer consumers. Originality/value – This research expands understanding of the consumer behaviours of US Baby Boomers related to fair trade. An additional contribution is the comparison of differences in fair trade knowledge, attitudes and behaviours of Early vs Late Baby Boomers. It also has potentially important implications for fair trade organizations, as the paper discusses marketing strategies specific to Baby Boomers.
Keywords: Consumer behaviour; Fair trade; Diffusion theory; Baby Boomers